Immobilization of hyperthermostable carboxylesterase EstD9 from Anoxybacillus geothermalis D9 onto Polymer material and its physicochemical properties - Mohd. Johan, Ummie Umaiera; Raja Abd. Rahman, Raja Noor Zaliha; Ahmad Kamarudin, Nor Hafizah; Latip, Wahhida; Mohamad Ali, Mohd Shukuri (Multidisciplinary Digital Publishing Institute, 2023)
Carboxylesterase has much to offer in the context of environmentally friendly and sustainable alternatives. However, due to the unstable properties of the enzyme in its free state, its application is severely limited. The present study aimed to immobilize hyperthermostable carboxylesterase from Anoxybacillus geothermalis D9 with improved stability and reusability. In this study, Seplite LX120 was chosen as the matrix for immobilizing EstD9 by adsorption. Fourier-transform infrared (FT-IR) spectroscopy verified the binding of EstD9 to the support. According to SEM imaging, the support surface was densely covered with the enzyme, indicating successful enzyme immobilization. BET analysis of the adsorption isotherm revealed reduction of the total surface area and pore volume of the Seplite LX120 after immobilization. The immobilized EstD9 showed broad thermal stability (10–100 °C) and pH tolerance (pH 6–9), with optimal temperature and pH of 80 °C and pH 7, respectively. Additionally, the immobilized EstD9 demonstrated improved stability towards a variety of 25% (v/v) organic solvents, with acetonitrile exhibiting the highest relative activity (281.04%). The bound enzyme exhibited better storage stability than the free enzyme, with more than 70% of residual activity being maintained over 11 weeks. Through immobilization, EstD9 can be reused for up to seven cycles. This study demonstrates the improvement of the operational stability and properties of the immobilized enzyme for better practical applications.